Samphire - Tee, George (Petits Propos Culinaires, 2024)
Two relatively common plants of the British coast bear the name samphire: rock samphire and marsh samphire. Confusion between them is common; all the more so since, although they belong to different botanical families (Umbelliferae and Chenopodiaceae respectively). they share some characteristics and disaster does not follow for the cook who uses 'the wrong one'. Recipes for pickled samphire abound in 17th and 18th century cookery books, and it seems clear that rock samphire was what authors of that era intended. Recipes are reappearing with increasing frequency in the 20th century, but now it is often apparent that marsh samphire is meant. In this article, Dr George Tee, who has been growing samphire in Devon and experimenting with both kinds in the kitchen, and who has also examined the history of samphire recipes over the centuries, does much to clear up the confusion. The drawings of the two sorts, from specimens which Dr Tee supplied, are by Soun. It would be interesting to have corresponding information about the use of samphire of either sort in other countries.